Considerações sobre a forma de operação de redes de P&D&I: um estudo de caso da Rede Mineral Escalab - Rolf Elias Gaspar (2023)
The formation of research networks has become an important R&D development mechanism in Brazil in recent years, as seen in the large number of public notices that finance R&D through networks. However, an important part of these networks does not, in fact, operate as a network, which carries out collaborative research, creating synergies to arrive at unique results that would only be possible through interaction. What seems to happen, in an important part of the cases, is that a group of researchers who gain public resources to set up a network, share these resources, work in isolation with few or no interaction and join their results to make a report at the end of the project. Another characteristic of these “research groups” is that they are usually completely dependent on public resources and focused on academic research. In this model, the group of researchers demobilizes right after the end of the resources. In this master's project we focus on the following research problems: How to stimulate, through public resources, the formation of a network that really operates as a network and how research networks, after the end of public funding, can continue to operate in a sustainable way, especially through interaction with the market/society to generate innovations. Therefore, the general objective of this work was to identify the mechanisms for structuring research networks that operate effectively in a collaborative way, generating R&D&I that impact society. For this, a case study was carried out considering the INCT Midas and Escalab that gave rise to the Candonga Network that became the Escalab Mineral Network. From the participation in the management of the Candonga Network, in the analysis of documents and interviews, four fundamental axes were identified for the operation of the research and innovation networks: (i) having the strong purpose of operating in a network, (ii) having quite clearly common objectives to be achieved, (iii) structure itself to operate as a network and (iv) seek other sources of funding. The present work analyzes these parameters that were considered critical for the formation of an R&D&I Network.